Nanomedicine Design of Particles, Sensors, Motors, Implants, Robots, and Devices. - Schulz, Mark J. (Artech House, 2009)
This forward-looking resource outlines the extraordinary new tools that are becoming available in nanomedicine. The book presents an integrated set of perspectives that describe where we are now and where we should be headed to put nanomedicine devices in to applications as quickly as possible, including consideration of the possible dangers of nanomedicine. Written by some of the most innovative minds in medicine and engineering, this unique volume helps you understand cutting-edge and futuristic areas of research that can have tremendous payoff in terms of improving human health. You find in.